The omega man [videorecording (DVD)] - Sagal, Boris, 1923-1981; Heston, Charlton; Zerbe, Anthony, 1936-; Cash, Rosalind; Laneuville, Eric; Koslo, Paul, 1944-2019-; Kilpatrick, Lincoln; Matheson, Richard, 1926-2013 (Distributed by Warner Home Video, 2007)
Welcome to the future where biological warfare has decimated life on Earth. Los Angeles is a windswept ghost town where Robert Neville tools his convertible through sunlit streets foraging for supplies. He fends off attacks by The Family-- sinister neopeople spawned by the plague. He also becomes a man with a mission after meeting Lisa, another infected survivor, and guardian of some healthy children representing our species' hope.